Comparative study of perovskite-type scintillator materials CsCaI3 and KCaI3 via first-principles calculations - Kang, Byungkyun; Feng, Qingguo; Biswas, Koushik (Journal of physics. D, Applied physics, 2018)
Several members of a large family of perovskite-like halides with a common chemical formula, ABX3 (A  =  monovalent, B  =  divalent, and X  =  halogen ion), are being investigated for their interesting properties and potential technological applications. CsCaI3 and KCaI3 are two such ionic compounds who are of interest in the quest for superior and cost-effective alternatives to NaI or CsI based scintillators. They are the subject of this first-principles based computational study. Both are wide-gap materials having primarily I 5p and Ca 3d characters near the valence and conduction band edges, respectively. Although built from [CaI6] octahedral motifs, structural differences between the two compounds is reflected in anisotropic electron effective mass and distinctive formation and migration of self-trapped holes. We discuss these properties as they relate to scintillation decay and proportional light yield.